Consumer response and its relationship with two sensorial characteristics of a beverage - Contreras-López, Eliana G. (2019)
The objective of this research was to determinate the consumer response about the degree liking of a beverage in function to flavor and consistency. The beverage was elaborated with pineapple (Ananas comosus) pulp/quinoa (Chenopodium quinoa Willd), in ratio 7:1 (w:w), processed in three heat treatments TP01, TP02 and TP03 (85 ºC x 26 minutes , 90 ° C x 7 minutes and 95 ° C x 2 minutes). The physical-chemical characteristics evaluated were: pH, degrees Brix, viscosity. The sensory evaluation was evaluating with trained judges (panel of 15 judges) to flavor and consistency. The results showed statistically significant differences between the three treatments in terms of viscosity and consistency; in flavor not showed statistically significant differences between treatments. The linking degree for consumers employed people of 16 to 40 years old. The consumer’s response not present significant differences. In conclusion, the consistency no was determinate in the consumer preference. Could be a correlation between the consumer’s preference and flavor. The female consumers and the younger consumers prefer the beverage.